FRI0200 Association of Serum DKK-1 and Sclerostin Levels with Acute Phase Reactants and Clinical and Radiographic Variables in Patients with Ankylosing Spondylitis. (9th June 2015) - Sakellariou, G.T.; Konsta, M.; Berberidis, C.; Iliopoulos, A.
Abstract : Objectives: To investigate the relationship of serum Dickkopf-1 (Dkk-1) and sclerostin levels with acute phase reactants and clinical and radiographic parameters in patients with ankylosing spondylitis (AS). Methods: This was an observational, cross-sectional study. Serum samples for total Dkk-1 and sclerostin were obtained from 65 tumour necrosis factor (TNF) inhibitor naïve patients with AS according to the modified New York criteria [mean age 41.3 years (S.D. 12.0); duration of symptoms 13.4 years (S.D. 10.0); male gender 61 patients (93.8%)]. The erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI) and modified Stroke AS Spine Score (mSASSS) were assessed for each patient. Subgroups were created by splitting ESR, CRP and BASDAI at predefined values considered as elevated for acute phase reactants and representing high and low disease activity for the BASDAI. ESR of 20mm/h, CRP levels of 5mg/l and BASDAI score of 40 were used as cutoff points. Results: Dkk-1 levels were significantly higher in patients with elevated ESR (p=0.009) and CRP (p=0.017) compared with those without (Table 1 ). Furthermore, Dkk-1 (p=0.005) and sclerostin (p=0.025) levels were significantly lower in patients with at least one syndesmophyte compared with those without. Dkk-1 levels were correlated negatively with age (r= −0.281, p=0.024), duration of symptoms (r= −0.282, p=0.023) and mSASSS (r= −0.253, p=0.042), and positively with sclerostin (r=0.557, p<0.001); and sclerostin levels were correlated negatively with age (r= −0.317, p=0.01) and mSASSS (r= −0.226, p=0.04), and positively with Dkk-1. Conclusions: Besides the negative association of serum Dkk-1 and sclerostin with radiographic damage, which is in accordance with the results of previous studies in AS, we found higher Dkk-1 levels in patients with elevated acute phase reactants, suggesting that the link between inflammation and systemic bone loss (osteoporosis) in AS could also be explained by the osteoblast inhibition through Wnt pathway, along with the osteoclast activation by pro-inflammatory cytokines like TNF. Thus, serum concentrations of Dkk-1 are appeared to relate not only to the specific anabolic process of syndesmophyte formation but also to the inflammation that affects the general bone remodeling. Disclosure of Interest: None declared